Self-Leadership dan Proactive Behavior pada Mahasiswa MBKM - Maharani, Liza Dwi; Nainggolan, Eben Ezer; Haque, Sayidah Aulia'ul (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2024)
This research aims to determine the relationship between self-leadership and proactive behavior in students participating in the MBKM program. This research uses quantitative correlational methods. The sampling technique used saturated sampling or total sampling with a sample of 135 students. The subjects in this research were students participating the MBKM program. The instruments in this research are the independent self- leadership scale and the proactive behavior scale. The data analysis technique uses simple linear regression analysis and shows a positive and significant relationship. This means that the higher the level of self-leadership a student has, the higher the student's proactive behavior will be. Keywords: MBKM, Proactive Behavior, Self-Leadership